Discover a wealth of knowledge at Westonci.ca, where experts provide answers to your most pressing questions. Find reliable answers to your questions from a wide community of knowledgeable experts on our user-friendly Q&A platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.

Does anyone know how to do this?

Does Anyone Know How To Do This class=

Sagot :

Answer:

A

Step-by-step explanation:

[tex]\dfrac{f(x)}{g(x)}=\dfrac{x+1}{x^{2}-x}\\f(x) = \dfrac{x+1}{x^{2}-x}*g(x)\\\\\dfrac{2}{x}*\dfrac{x^{2}-x}{x+1}=g(x)\\\\\\\dfrac{2}{x}*\dfrac{x(x-1)}{x+1}=g(x)\\\\\\\dfrac{2(x-1)}{x+1}=g(x)\\\\\[/tex]